1982
DOI: 10.1093/nar/10.6.2163
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements of (2′–5′) oligoadenylate for protein synthesis inhibition in human fibroblasts

Abstract: The structural requirements of (2'-5')-oligoadenylic acid (pppA(2'p5'A)x, X greater than or equal to 1 or (2'-5'An) for inhibition of protein synthesis in cells were examined with a modified calcium-coprecipitation technique, using a series of trinucleotide analogs (pppA2'p5'A2'p5'N, N=rC, rG, rU, T, dC, dG, dA). In this system both the degree and the duration of the inhibition of protein synthesis were dependent on the added concentration of (2'-5')A3. Of all the heterotrimers, only the deoxy A derivative was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Control cultures were treated with calcium phosphate, but without oligonucleotides and the incorporation of [35S]methionine into control cultures was taken as 100%. shown), in agreement with [9] on HF926 cells. (2' -5 ')p33 'dA4 either enzymatically or chemically synthesized is as good as or a better inhibitor of protein synthesis than is (2' -5 ')p& in lysates from rabbit reticulocytes [7].…”
Section: Cellsupporting
confidence: 86%
See 2 more Smart Citations
“…Control cultures were treated with calcium phosphate, but without oligonucleotides and the incorporation of [35S]methionine into control cultures was taken as 100%. shown), in agreement with [9] on HF926 cells. (2' -5 ')p33 'dA4 either enzymatically or chemically synthesized is as good as or a better inhibitor of protein synthesis than is (2' -5 ')p& in lysates from rabbit reticulocytes [7].…”
Section: Cellsupporting
confidence: 86%
“…The continued action of the endonuclease and the prolonged maintenance of protein synthesis inhibition may require a constant presence of (2' -5 ')psA. [9]. Thus, an analog of (2' -5 ')psA.…”
Section: The Prolonged Inhibition Of Protein Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…As regard the role of the adenine rings in 2‐5A, it has been reported that RNase L has drastically lower affinity for cytidine, uridine, or inosine analogs, [10] in Figure 5D, compared to its adenine counterpart [6] (Torrence et al , 1984). Similarly, [11] failed to activate RNase L (Drocourt et al , 1982). Torrence et al (1984) suggested that RNase L interacts with N1 and/or N6 of the adenine ring of 2‐5A.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the biological role of 2′,5′-linked heteronucleotides, which might be synthesized in cells, is not known [1,15,20,21]. …”
Section: Introductionmentioning
confidence: 99%